MICROSPORE ANALYSIS FOR GENOTOXICITY OF POLLUTED ATMOSPHERIC ENVIRONMENT (THE CASE STUDY IN THE MATARAM CITY) - Suripto Suripto; Kurniasih Sukenti; Sukiman Sukiman; Immy Suci Rohyani; Ahmad Jupri (Jurnal Biologi Tropis, 2019)
Abstract : The need for environmental protection continues to increase, so exploratory studies of agents of polluted environmental indicators are becoming increasingly important. The advantages of using flowering plants for environmental bio-indicator studies include the availability of sufficient test material with their variations and the availability of different periods for sampling. Seven plant species were used to examine their suitability as bio-indicator for genotoxicity of polluted atmospheric environment in Mataram City by microspore analysis. This study was conducted with the aim of, 1) knowing the level of difference in the frequency of failure (abortiveness) of microspores between similar plants that grow in areas at risk of being polluted in the city and those growing in areas not at risk of being polluted outside the city of Mataram, and 2) find out what types of flowering plants, especially those in city parks that are suitable as bio-indicators of air pollution for Mataram City. The percentage of aborted pollens was calculated out of 50 to 300 observed pollen grains of each selected individual flowering plant. Sample of each plant species from every study area consist of ten plant individuals. Data were analyzed by use the Wilcoxon one way-test at a 0.05 to determine significance of difference in the percentage of aborted pollen grains from same plant species between in the risky polluted area and plant in the control area.ÃÂ  The results showed that Lantana camara L. is suitable as bio-indicator for atmospheric pollution in Mataram City or other cities that have a density of traffic flow of motorized vehicles around 100 vehicles per hour. Its percentage of aborted pollen grains is 1,62 ÃÂ±ÃÂ  0,08 % in the risky polluted area,ÃÂ  andÃÂ ÃÂ  1,21 ÃÂ± 0,13 % in the control area. Others six observed plant spesies, i.e.ÃÂ  Acacia auriculiformis A. Conn. Ex Bth., Bauhinia acuminata L., Baugenvillea spectabilis Willd. Duranta erecta L., Ixora coccinea L. and Rosa hybryda Hort., each of them is not suitable as bioindicator for it. Their percentage of pollen abortiveness in polluted and not-polluted areas were not different, significantly.Keywords: Genotoxicity, Microspores, Polluted air environment